2016
DOI: 10.3310/hta20730
|View full text |Cite
|
Sign up to set email alerts
|

An international randomised controlled trial to compare TARGeted Intraoperative radioTherapy (TARGIT) with conventional postoperative radiotherapy after breast-conserving surgery for women with early-stage breast cancer (the TARGIT-A trial)

Abstract: BackgroundBased on our laboratory work and clinical trials we hypothesised that radiotherapy after lumpectomy for breast cancer could be restricted to the tumour bed. In collaboration with the industry we developed a new radiotherapy device and a new surgical operation for delivering single-dose radiation to the tumour bed – the tissues at highest risk of local recurrence. We named it TARGeted Intraoperative radioTherapy (TARGIT). From 1998 we confirmed its feasibility and safety in pilot studies.ObjectiveTo c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 136 publications
3
62
0
1
Order By: Relevance
“…The planned follow-up for trial participants was at least 10 years. 69 Median follow-up achieved for the most recent 2014 publication 65 is 2 years 5 months.…”
Section: Designmentioning
confidence: 99%
See 3 more Smart Citations
“…The planned follow-up for trial participants was at least 10 years. 69 Median follow-up achieved for the most recent 2014 publication 65 is 2 years 5 months.…”
Section: Designmentioning
confidence: 99%
“…The trial protocol specifically defined early invasive breast cancer as T1 and small T2, N0-1, M0. 69 The initial trial publication 64 stipulated the pre-operative diagnosis of lobular carcinoma as a single exclusion criterion, although the trial protocol specified additional exclusion criteria. 69 Furthermore, because the trial was pragmatic, each participating centre had the option to predefine more restrictive entry criteria than in the core protocol (e.g.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, Bekelman et al 24 reported an increase of use of hypofractionation for breast cancer in the US from 10.6% in 2008 to 34.5% in 2014 24 . The calculation of adjusted mean total healthcare expenditures in the first year after diagnosis was highly relevant, resulting as $28,747 for hypofractionation vs $31,641 for conventional breast irradiation (D$2,894; p < .001), representing a decrease of 10%, by reducing the number of fractions from 25-39 to 11-24. In terms of irradiation modality, the multi-center international TARGIT-A trial 25 has recently shown that x-rays intraoperative radiotherapy (IORT) in single shot was less costly than EBRT and produced slightly more QALYs than conventional radiotherapy. The authors underline that "TARGIT had a positive incremental net monetary benefit that was borderline statistically" and "when TARGIT was used instead of conventional radiotherapy in suitable patients (age >45 years), it might potentially reduce costs to healthcare providers by £8-9.1 million each year".…”
mentioning
confidence: 99%